Clinical applications of circulating biomarkers in non-small cell lung cancer - Oh, Hyun-Ji; Imam-Aliagan, Abdulhamid B.; Kim, Yeo-Bin; Kim, Hyun-Jin; Izaguirre, Issac A.; Sung, Chang K.; Yim, Hyungshin (Frontiers in Cell and Developmental Biology, 2024)
Despite recent advances in cancer diagnostics and treatment, the mortality associated with lung cancer is still the highest in the world. Late-stage diagnosis, often accompanied by metastasis, is a major contributor to the high mortality rates, emphasizing the urgent need for reliable and readily accessible diagnostic tools that can detect biomarkers unique to lung cancer. Circulating factors, such as circulating tumor DNA and extracellular vesicles, from liquid biopsy have been recognized as diagnostic or prognostic markers in lung cancer. Numerous clinical studies are currently underway to investigate the potential of circulating tumor DNA, circulating tumor RNA, exosomes, and exosomal microRNA within the context of lung cancer. Those clinical studies aim to address the poor diagnostics and limited treatment options for lung cancer, with the ultimate goal of developing clinical markers and personalized therapies. In this review, we discuss the roles of each circulating factor, its current research status, and ongoing clinical studies of circulating factors in non-small cell lung cancer. Additionally, we discuss the circulating factors specifically found in lung cancer stem cells and examine approved diagnostic assays designed to detect circulating biomarkers in lung cancer patients.